A novel compound heterozygous variant of ECEL1 induced joint dysfunction and cartilage degradation: a case report and literature review - Jing, Siyuan; Peng, Mou; He, Yuping; Hua, Yimin; Li, Jinrong; Li, Yifei (Frontiers in Neurology, 2024)
Background Distal arthrogryposis type 5D (DA5D) represents a subtype of distal arthrogryposis (DA) characterized by congenital joint contractures in the distal extremities. DA5D is inherited in a rare autosomal recessive manner and is associated with the ECEL1 gene. In this report, we describe a case of an infant with bilateral knee contractures and ptosis, caused by a novel compound heterozygous mutation of ECEL1. Case presentation We conducted DNA extraction, whole-exome sequencing analysis, and mutation analysis of ECEL1 to obtain genetic data on the patient. We subsequently analyzed the patient’s clinical and genetic data. The proband was a 6 months-old male infant who presented with significant bilateral knee contracture disorders and bilateral ptosis. MRI demonstrated cartilage degradation in knee joint. Whole-exome sequencing of the patient’s DNA revealed a compound heterozygous mutation of c.2152-15C>A and c.110_155del in ECEL1. Analysis with the MutationTaster application indicated that c.110_155del was pathogenic (probability = 1), causing frameshift mutations affecting 151 amino acids (p.F37Cfs*151). The truncated protein lost the substructure of a transmembranous site based on the predicted protein crystal structure AF-O95672-F1. The variant of c.2152-15C>A of ECEL1 was also predicted to be disease-causing (probability = 0.98) as it impaired the methylation of ECEL1 serving as an H3K27me3 modification site, which led to the dysfunction of the second topological domain. Therefore, we concluded that the compound heterozygous mutation caused the pathogenic phenotype of this proband. Conclusion The present case highlights the usefulness of molecular genetic screening in diagnosing unexpected joint disorder. Identification of novel mutations in the ECEL1 gene broadens the mutation spectrum of this gene and adds to the genotype-phenotype map of DA5D. Furthermore, rapid whole-exome sequencing analysis enabled timely diagnosis of this rare disease, facilitating appropriate treatment and scheduled follow-up to improve clinical outcomes.